(3QSGdI aj GdYed HGdQHY GdeQShe HGdebfWQGJs - (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdMeO (B: (3agPg QSGdI ai GdYed HGdQHY GdehShe HGdebfWQGJ hVYJgG ddeHJOF s
(3BNQgG (B:s
(3hcPdc JaYd HeWGdY WdhYg heWGdY ZQhHg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B46 - (3U(B49s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B49 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B105) s
Keywords: (3Gdadcs